Development of Attendance Monitoring System with Artificial Intelligence Optimization in Cloud - Naen, Mohamad Fakir; Muhamad Adnan, Muhamad Hariz; Yazi, Nurul Adilah; Nee, Chee Ken (International Journal of Artificial Intelligence, 2021)
The creation of an attendance management system based on biometrics is proposed in this research. Keeping track of student attendance during lecture periods has proven to be a difficult task. Because human calculating creates errors and wastes a lot of time, the capacity to compute the attendance percentage becomes a key challenge. For this reason, a biometric-based attendance management system is being developed. This system uses a fingerprint device to take attendance electronically, and the attendance records are kept in a database. Following student identification, attendance is recorded. Artificial intelligence is also proposed as a component of the system. The system will aid in the reduction of errors and the more effective compilation of attendance data.